A TREATISE ON CONTEMPORARY WORLD ‘AGE OF ANYTHING – CAN – HAPPEN’‘THE TALE OF THE SEEKER THE GRAIL OF LOVE’ - P. Suneetha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rushdie’s latest novel Quichotte1 a literary “embarrass de richesse,”2 runs like a picaresque novel of the Spanish writer’s Don Quixote3 of Miguel de Cervantes Saavedra of the 16th century. In fact, it is a strikingly reworking of Cervantes’s work Don Quixote and “a retelling of it and a homage to it.”4 It almost runs like a comic romance that influenced many writers5 at a later date including Sam Du Champ, a mediocre writer of spy thrillers. In the Spanish romance Don Quixote, has had his wits disordered by inordinate devotion to the tales of chivalry and he calls up on to roam the world in search of adventures on his old nag Rocinat. Accompanied by Sancho Panza, his squire, he, with a view to continuing chivalric tradition, elects a beautiful damsel to be the mistress of the heart. So the most commonplace objects assume in his imagination fearful or romantic forms. He names the peasant girl from a neighbouring village Dulcinea del Toboso an honour about which she is entirely unaware. To set right his mental condition, Sanson Carraseo one of his friends, disguises himself as a knight and defeats Don Quixote who is forced to spend his time to lead the life of a shepherd. On his return journey, he dies though many lengthy digressions enrich the plot of the novel. The Spanish novel with its gripping theme of the confrontation of illusion with reality, bore deep impress on multitudes of writers including Salman Rushdie.